2011
DOI: 10.1111/j.1468-3083.2011.04265.x
|View full text |Cite
|
Sign up to set email alerts
|

Skin manifestations of obesity: a comparative study

Abstract: Obesity is strongly related to several skin alterations that could be considered as markers of excessive weight. Skin care of obese patients deserves particular attention, not only because of the high prevalence of cutaneous alteration but mainly because many of these disorders are preventable and could be treated, improving patient's quality of life.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
51
15
6

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(84 citation statements)
references
References 25 publications
9
51
15
6
Order By: Relevance
“…10 Acanthosis nigricans (hyperpigmented velvety cutaneous thickening affecting localized areas of the skin) is frequently associated with obesity, endocrinopathies, malignancy, genetic syndromes and some drugs use. 13 Acanthosis nigricans in the present study was prevalent among 53.6% of the studied group, which was lower than the findings from studies conducted in Brazil (76%), 11 USA (74%), 12 , and Mexico (64.2%), 8 but higher than those found in Kuwait (33%) 10 , and Saudi Arabia(14.1%). 15 This variation in prevalence rate might be attributed to the variation of age groups and the severity of obesity among the subjects of the mentioned studies.…”
Section: Resultscontrasting
confidence: 77%
See 2 more Smart Citations
“…10 Acanthosis nigricans (hyperpigmented velvety cutaneous thickening affecting localized areas of the skin) is frequently associated with obesity, endocrinopathies, malignancy, genetic syndromes and some drugs use. 13 Acanthosis nigricans in the present study was prevalent among 53.6% of the studied group, which was lower than the findings from studies conducted in Brazil (76%), 11 USA (74%), 12 , and Mexico (64.2%), 8 but higher than those found in Kuwait (33%) 10 , and Saudi Arabia(14.1%). 15 This variation in prevalence rate might be attributed to the variation of age groups and the severity of obesity among the subjects of the mentioned studies.…”
Section: Resultscontrasting
confidence: 77%
“…It is considered as a stigma of morbid obesity resulting from the effect of the pressure of excess weight. It was found that the prevalence rate of planter hyperkeratosis in the present study lower than that reported among obese adults in Mexico (75.2%) 8 but higher than those shown in Brazil (46.7%), 11 and Kuwait (45.1%). 10 Skin tags (61.2%) in the present study were found to be lower than that reported among obese adults in the USA (74%), 12 but higher than those shown in Brazil (47.94%), 11 and Kuwait (30%).…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…Psödoakantozis nigrikanslı kadın ve erkek oranları ise %59 ve %41 olarak saptanmıştır. Literatürdeki bir diğer çalışmada obezlerin %27,6'sında psödoakantozis nigrikans görülürken, kontrol grubunda psödoakantozis nigrikansa rastlanmamıştır 14 . Çalışmamızda beşinci sırada görülen psödoakantozis nigrikans, obez grupta aşırı kilolu grup ve kontrol grubundan istatistiksel olarak anlamlı derecede yüksek tespit edildi.…”
Section: Bulgularunclassified
“…Recent research has shown that it affects many different patient populations and that people are found throughout the health systems (1) (2) . The cause of chronic oedema is often complex and includes: damage to lymphatics during cancer treatment, primary lymphoedema (due to problems in the development of the lymphatic system); damage to the venous system (phlebo-lymphoedema) and obesity (3), (4), (5), (6). It occurs in those with chronic diseases affecting mobility such as spina bifida, multiple sclerosis and rheumatoid arthritis and in cardiovascular diseases (7)(8)(9) (2) .…”
Section: Introductionmentioning
confidence: 99%